Genetic suppressors of Δgrx3 Δgrx4, lacking redundant multidomain monothiol yeast glutaredoxins, rescue growth and iron homeostasis. Issue 6 (30th June 2022) - Li, Guichun; Nanjaraj Urs, Ankanahalli N.; Dancis, Andrew; Zhang, Yan
Abstract: Saccharomyces cerevisiae Grx3 and Grx4 are multidomain monothiol glutaredoxins that are redundant with each other. They can be efficiently complemented by heterologous expression of their mammalian ortholog, PICOT, which has been linked to tumor development and embryogenesis. PICOT is now believed to act as a chaperone distributing Fe-S clusters, although the first link to iron metabolism was observed with its yeast counterparts. Like PICOT, yeast Grx3 and Grx4 reside in the cytosol and nucleus where they form unusual Fe-S clusters coordinated by two glutaredoxins with CGFS motifs and two molecules of glutathione. Depletion or deletion of Grx3/Grx4 leads to functional impairment of virtually all cellular iron-dependent processes and loss of cell viability, thus making these genes the most upstream components of the iron utilization system. Nevertheless, the Δgrx3/4 double mutant in the BY4741 genetic background is viable and exhibits slow but stable growth under hypoxic conditions. Upon exposure to air, growth of the double deletion strain ceases, and suppressor mutants appear. Adopting a high copy-number library screen approach, we discovered novel genetic interactions: overexpression of ESL1, ESL2, SOK1, SFP1 or BDF2 partially rescues growth and iron utilization defects of Δgrx3/4 . This genetic escape from the requirement for Grx3/Grx4 has not been previously described. Our study shows that even a far-upstream component of the iron regulatory machinery (Grx3/4) can be bypassed, and cellular networks involving RIM101 pH sensing, cAMP signaling, mTOR nutritional signaling, or bromodomain acetylation, may confer the bypassing activities.